KEPERCAYAAN ATASAN, PENGALAMAN KERJA DAN KINERJA - Karvy, Rein Rizka (JIANA ( Jurnal Ilmu Administrasi Negara ), 2016)
Trust Boss, Work Experience and Performance. This study aims to determine the trust boss, work experience and performance in Pekanbaru city urban village secretary, as well as to determine the effect of trust boss and secretary work experience on the performance ravine in Pekanbaru. The method used in this research is quantitative research methods. The population in this study are all lurah secretary in the city of Pekanbaru, amounting to 58 and completely sampled. Data collection techniques using the technique of questionnaires, while data analysis technique using product moment correlation technique. Based on the results of research known to the secretary boss reposal ravine with a score of 3.2, which means that the trust boss to the secretary of the ravine in Pekanbaru is good, then the secretary work experience ravine with a score of 2.8, which means that t he work pengelaman owned secretary ravine is enough both secretary and performance ravine with a score of 2.9 means that the performance sekretris headman in the works can be seen already quite good. While the influence of the trust factor and the experience of the performance is positive and significant.